Microsurgical Resection of Glioblastoma in a Patient Infected with Covid-19: A Case Report - Macêdo, Lívio Pereira de; Franke, Kauê; Cezar-Junior, Auricélio Batista; Faquini, Igor Vilela; Carvalho, Eduardo Vieira de, Júnior; Almeida, Nivaldo S.; Azevedo-Filho, Hildo Rocha Cirne (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
The COVID-19 pandemic has affected a large number of patients in all countries, overwhelming healthcare systems worldwide. In this scenario, surgical procedures became restricted, causing unacceptable delays in the treatment of certain pathologies, such as glioblastoma. Regarding this tumor with high morbidity and mortality, early surgical treatment is essential to increase the survival and quality of life of these patients. Association between COVID-19 and neurosurgical procedures is quite scarce in the literature, with a few reported cases. In the present study, we present a rare case of a patient undergoing surgical resection of glioblastoma with COVID-19.
Keywords: neurosurgery; COVID-19; SARS-CoV-2; glioblastoma